A Rare Case of Nail Lichen Planus - Nolanda Trikanti; Rina Gustia; Tutty Ariani; Mutia Sari (HM Publisher, 2023)
Background: Nail lichen planus (NLP) is often associated with the involvement of other mucocutaneous sites. Though isolated nail involvement can be seen in a number of cases, it is seen in up to 10% of cases. Nail lichen planus is a rare case. This is the first case in the last 5 years in the dermatology and venereology department of Dr. M. Djamil Hospital Padang. Case presentation: A 26 years old woman came to the Dermatology and Venereology Department at Dr. M. Djamil Hospital Padang with all of her fingernails and toenails ridging, thinning, and brittle, and the color became yellow brown-blackish that worsened 6 months ago. This complaint had been suffered for 5 years ago. Dermatological examination showed onychodystrophy, longitudinal ridging and fissuring, yellow-brownish blackish discoloration on all fingernails and toenails, and there were no skin and mucosa lesions. The dermatology life quality index (DLQI) patient was 8. Potassium hydroxide (KOH) examination and fungal culture were negative. Histopathological examination showed hypergranulosis and sawtooth rete ridges. The patient was treated with clobetasol propionate 0,05% ointment with occlusion twice per day and showed improvement. Conclusion: Nail lichen planus can occur in the absence of skin or mucosal involvement. In this case, there is no skin or mucosal involvement. The diagnosis in this case is based on clinical, dermoscopic, and histopathological examination.